Open Access Initiative and its Effect on the Quality of Scholarly Communication - Agyei, Emelia A. O.; Pullen, Craig (Ghana Library Journal, 2009)
The purpose of this paper is to provide an overview of how the Open Access (OA) Initiative affects the quality of scholarly literature. Content analysis was the methodology used to analyze information resources. Mostly peer-reviewed articles published between the years 2000-2006 that discuss the Open Access (OA) Movement and its effects on the quality of scholarly communication were used. The peer-review process was critically analyzed for the importance it plays in scholarly literature. The findings indicate that the present business model of the OA Initiative gives cause to doubt the quality of research articles published in the medium (OA). As much as advocates of the OA Movement do not approve of this opinion, they acknowledge this as a major challenge facing the movement.